PERTANGGUNG JAWABAN HUKUM KONSULTAN KONSTRUKSI TERHADAP KEGAGALAN KONSTRUKSI BANGUNAN - Linggomi Adinda Tamaradhina Napitupulu, (Magister Hukum Universitas Semarang, 2024)
The purpose of the research is to study and analyze the implications of the Construction Services Law, namely Law Number 2 of 2017, which is updated by Law Number 6 of 2023 concerning the Stipulation of Government Regulations instead of Law Number 2 of 2022 concerning Job Creation, especially regarding the application of building failure provisions stipulated in the second segment of Article 60 of Law Number 2 of 2017 with building failure arrangements stipulated in construction work contracts. The assessment of the circumstances declared as the occurrence of construction failure begins after the service provider (construction contractor) carries out the second handover process for the work he has carried out, and in less than 10 years, there is a building collapse and the malfunction of the building being handed over. Business actors in the construction industry in Indonesia are bound by a construction work contract signed by the parties. This research will present information on how the provisions of building failure are regulated in the contract made between construction service users and construction service providers. Service users in construction projects can be in the form of government agencies and other private companies, while construction service providers such as construction implementation contractors and construction consulting companies (planning consultants, supervisory consultants, and other consultants). The conclusion of this research is expected to anticipate deviations from the provisions regarding building failure in the preparation of construction work contracts.